A tale of two Koreas: Property rights and fairness - Syngjoo Choi; Byung-Yeon Kim; Jungmin Lee; Sokbae Lee (Centre for Microdata Methods and Practice (cemmap), 2019)
We compare two groups of the non-student Korean population - native-born South Koreans (SK) and North Korean refugees (NK) - with contrasting institutional and cultural backgrounds. In our experiment, the subjects play dictator games under three different treatments in which the income source varies: first, the income is randomly given to the subject; second, it is earned by the subject; third, it is individually earned by the subject and an anonymous partner and then pooled together. We find that preferences for giving depend on the income source in different ways for the SK and NK subjects. The SK subjects become more selfish when the income is individually earned than when it is gifted to them. Furthermore, the NK subjects are not responsive to the earned income treatment but behave more pro-socially when individually earned incomes are pooled. The NK subjects behave in a more self-interested manner when they participated in market activities in North Korea.
Keywords: C92; C93; D03; P20; 330; Selfish Behavior; Institutions; Division of Korea; Dictator Game; Earnings; Market Activities